2018
DOI: 10.15537/smj.2018.9.22573
|View full text |Cite
|
Sign up to set email alerts
|

The breast lesion excision system procedure: An optimal solution for the management of indeterminate BI-RADS category 3 breast lesions in women with severe anxiety

Abstract: Objectives:To evaluate the efficacy of the Breast lesion excision system (BLES) procedure as a primary excisional biopsy for the management of breast imaging-reporting and data system (BI-RADS) category 3, small, and solid breast lesions in women having severe breast cancer anxiety.Methods:A retospective study was conducted on 68 patients who underwent a BLES procedure. The study protocol was approved by the local ethical committee of Yeni Yuzyıl University in Istanbul, Turkey. The study was carried out accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Krainick-Strobel et al as well as Liu et al reported that the VAB biopsy was associated with a low risk of side effects, such as hematoma at the biopsy site in 5.52% of cases, which did not require a surgical intervention [9,10]. The same results can be found in studies analyzing complications of the BLES procedure with occurrence of hematoma at the biopsy site not requiring intervention in 4.2-5.5% of cases [11][12][13][14]. Our study did not reveal any severe early or late side effects requiring intervention, either in the VAB or the BLES biopsy patients.…”
Section: Discussionmentioning
confidence: 77%
“…Krainick-Strobel et al as well as Liu et al reported that the VAB biopsy was associated with a low risk of side effects, such as hematoma at the biopsy site in 5.52% of cases, which did not require a surgical intervention [9,10]. The same results can be found in studies analyzing complications of the BLES procedure with occurrence of hematoma at the biopsy site not requiring intervention in 4.2-5.5% of cases [11][12][13][14]. Our study did not reveal any severe early or late side effects requiring intervention, either in the VAB or the BLES biopsy patients.…”
Section: Discussionmentioning
confidence: 77%
“…If we can screen category 3 and category 4 of patients and observe the low-risk lesions regularly, the unnecessary invasive examination can be reduced 5,6 . If these low-risk breast lesions affect the patient's daily life and physical and mental health, surgical resection is generally recommended 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The unnecessary invasive examination can be minimized by screening and observing category 3 and category 4a patients on a regular basis ( 7 , 8 ). Surgical resection is typically advised if the patient’s daily life, physical health, or mental health are affected by these low-risk breast lesions ( 9 ).…”
Section: Introductionmentioning
confidence: 99%